PENGARUH VARIASI BEBAN PLTG TERHADAP KINERJA HRSG DARI PLTGU - Aziz, Amiral; Suwarna, Suwarna (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
In a combined cycle power plant without supplementary firing, the efficiency ofthe plant dependsmainly on the efficiency ofgas turbine powerplant. The power plant will be able to run over awide range i.erunfew gas turbines and opearting the remaining gas turbine at the highest efficiency close to thefull load.This paper presents some results ofstudy that carried out to evaluate the effect ofload variation ofthe GasTurbine Power Plant on the performance ofHeat Recovery Steam Generator ofthe combined cycle powerplant.